Hubungan Lama Paparan Dan Intensitas Kebisingan Terhadap Gangguan Pendengaran Akibat Bising - Nauval Halim; Indra Setiawan; Rubayat Indradi (Perhimpunan Dokter Kedokteran Komunitas dan Kesehatan Masyarakat Indonesia (PDK3MI), 2022)
One of the most common occupational diseases is noise-induced hearing loss. Noise-induced hearing loss is a decrease in the function of the sense of hearing caused by exposure to noise. Noise exposure greater than 85 dB and exposure for more than 8 hours will increase the risk of hearing loss. Hearing loss due to noise can cause an increase in the risk of work-related accidents which will have an impact on the safety of workers or the community. The purpose of this publication is to determine the relationship between duration of exposure and noise intensity to noise-induced hearing loss. The library method used is in the form of 31 literature sources consisting of 8 textbooks and 23 national and international journals with a time span of 2013-2020. From the results of the analysis there is a relationship between the length of exposure and the intensity of noise on the hearing loss of factory workers. It can be concluded that the duration of exposure and the intensity of noise affect hearing loss due to noise. Other factors that can affect the occurrence of hearing loss due to noise such as age, habits outside of work, and the use of PPE can also affect the occurrence of hearing loss due to noise.